Media for equity: uma proposta de definição teórica e de contribuições à prática gerencial a partir de experiências de startups brasileiras - Silveira, Vitor da Cunha (2023)
The global growth of digital media consumption in recent decades has caused advertising budgets to migrate from traditional media such as TV to new digital platforms. In addition, it gave rise to the phenomenon of influencers who started to use their digital social networks as true media vehicles. In this context, traditional companies are using their idle inventory as a bargaining chip to buy equity stakes in startups. The same happens with influencers who are becoming partners of these companies, exchanging advertising on their networks for these slices of business. This phenomenon of exchanging media for shares is what we are calling Media for Equity (MxE or M4E). This study, divided into 3 articles or chapters, seeks in the first one, in the light of the risk investment and marketing literature, to expand the concept of MxE, bringing in addition to the financial investment represented by the media value, the non-financial investments (Smart Money) represented, among other attributes, for credibility and the investor's network of relationships, but, mainly, for the development of marketing capabilities in the onslaught. In the following articles, a multiple case study was carried out, interviewing 14 representatives of Brazilian companies that were investors, investees and intermediaries in the process. This material was analyzed using the Atlas.TI software through the co-occurrence of citations coded from deductive codes from the literature of the first article and inductive codes that emerged during the field research. Thus, in the second article we show the importance of non-financial resources as a differential for the search for the model, and among them, mainly, the development of marketing capabilities; the role of the advisor within the investor as an accelerator of this capacity building of the investee; and the different metrics used and the investor's role in reinforcing, in addition to short-term visions of growth, but also brand building as a partnership objective. Finally, the third article contributes to managerial practice by bringing a proposal for an MxE model to different types of investors. The work also contributes to the practice by expanding the definition of MxE adopted by practitioners by including smart money as part of the MxE agreement. And it fills the gap in the literature by including MxE within the venture investment model, and by merging this investment process with the influence marketing process, thus bringing these influencers to the role of angel investors.